2016
DOI: 10.1016/j.toxrep.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Specific long non-coding RNAs response to occupational PAHs exposure in coke oven workers

Abstract: HighlightsHOTAIR and MALAT1 were upregulated in PBLCs of PAHs-exposed workers.HOTAIR and MALAT1 expression was positively associated with the degree of DNA damage induced by PAHs.H3K27me3 modification was positively correlated with the degree of genetic damage and the increase of HOTAIR expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…The expression of MALAT1 in the cerebellum, hippocampus, and brain stem of human alcoholics is significantly increased, which may be involved in the chronic injury of alcohol to brain tissue (Kryger et al, ). MALAT1 expression in coke oven workers is also increased after occupational exposure to polycyclic aromatic hydrocarbons (PAHs), and MALAT1 might be involved in response to PAHs‐induced DNA damage (Gao et al, ). Arsenite may induce the upregulation of MALAT1, which in turn increases glycolysis by stabilizing hypoxia‐inducible factor 1α (HIF‐1α) expression (Luo et al, 2016).…”
Section: Role Of Malat1 In Cellular Stress Responsesmentioning
confidence: 99%
“…The expression of MALAT1 in the cerebellum, hippocampus, and brain stem of human alcoholics is significantly increased, which may be involved in the chronic injury of alcohol to brain tissue (Kryger et al, ). MALAT1 expression in coke oven workers is also increased after occupational exposure to polycyclic aromatic hydrocarbons (PAHs), and MALAT1 might be involved in response to PAHs‐induced DNA damage (Gao et al, ). Arsenite may induce the upregulation of MALAT1, which in turn increases glycolysis by stabilizing hypoxia‐inducible factor 1α (HIF‐1α) expression (Luo et al, 2016).…”
Section: Role Of Malat1 In Cellular Stress Responsesmentioning
confidence: 99%
“…However, all these results further confirm the presence of PAHs in trace amount irrespective of medium. Study on the health effects of PAHs external and internal occupational exposure on DNA damage and RNAs response in coke oven workers [ 38 ]; and in smoked fish species from markets in Southern Nigeria have also been investigated [ 39 ]. High exposure to PAHs could lead to lower Intelligent Quotient (IQ) and childhood asthma [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other than MEG3, dysregulations of many lncRNAs in lung cancer have been identified and summarized by Khandelwal et al [32,106], of which some have been shown to be associated with occupational PAH (Polycyclic Aromatic Hydrocarbon) exposures in coke oven workers, such as HOTAIR, TUG1, MALAT1 and GAS5 [107]. Cadmium was also found to induce the expression of lncRNA, ENST00000414355, to modulate DNA damage and repair in 16HBE cells.…”
Section: Tumor Suppressor Gene and Proto-oncogene Alterationsmentioning
confidence: 99%